Effect of a clockwise‐locked deletion in FliG on the FliG ring structure of the bacterial flagellar motor. (6th February 2018) - Kinoshita, Miki; Namba, Keiichi; Minamino, Tohru
Abstract : FliG is a rotor protein of the bacterial flagellar motor. FliG consists of FliGN, FliGM and FliGC domains. Intermolecular FliGM –FliGC interactions promote FliG ring formation on the cytoplasmic face of the MS ring. A conformational change in HelixMC connecting FliGM and FliGC is responsible for the switching between the counterclockwise (CCW) and clockwise (CW) rotational states of the FliG ring. However, it remains unknown how it occurs. Here, we carried out in vivo disulfide cross‐linking experiments to see the effect of a CW‐locked deletion (∆PAA) in FliG on the FliG ring structure in Salmonella enterica . Higher‐order oligomers were observed in the membrane fraction of the fliG (∆PAA + G166C/G194C) strain upon oxidation with iodine in a way similar to FliG(G166C/G194C), indicating that the PAA deletion does not inhibit domain‐swap polymerization of FliG. FliG(∆PAA + E174C) formed a cross‐linked homodimer whereas FliG(E174C) did not, indicating that Glu174 in HelixMC of one FliG protomer is located much closer to that of its neighboring subunit in the CW motor than in the CCW motor. We will discuss possible helical rearrangements of HelixMC that induce a structural remodeling of the FliG ring upon flagellar motor switching. Abstract : A conformational change of HelixMC may allow FliGC domains to swap their binding partners from its neighboring FliGM domain on their left side to that on their right side when the motor switches its rotational direction from CCW to CW.